2014
DOI: 10.37761/rsqp.v80i4.182
|View full text |Cite
|
Sign up to set email alerts
|

Determinación De Compuestos Fenólicos, Flavonoides Totales Y Capacidad Antioxidante en Mieles Peruanas De Diferentes Fuentes Florales

Abstract: Se realizó el estudio en doce mieles de diferentes marcas colectadas en supermercados de Lima, determinándose el contenido de compuestos fenólicos totales según Pérez et al, flavonoides totales por Zhishen et al, ensayo de 2-desoxi-D-ribosa por Sandoval et al, capacidad antioxidante por el método ABAP/ABTS, según Overveld et al., su efecto antioxidante sobre el anión superóxido según Bermúdez-Campos et al y contenido de fenólicos por HPLC según Muñoz et al. La miel silvestre del callejón de Huaylas tuvo mayor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 1 publication
0
8
0
5
Order By: Relevance
“…In Kosovo, Ibrahimi & Hajdari, [ 104 ] observed a lower TPC in the multifloral acacia (25.76 ± 10.16 mg GAE/100 g) and chestnut (35.77 ± 8.26 mg GAE/100 g) honeys, but with a lower variation among samples, compared to the multifloral from meadows (46.48 ± 16.59 mg GAE/100 g) and forests (46.33 ± 18.95 mg GAE/100 g). Muñoz et al [ 56 ] reported that the wild multifloral of Peru registered a higher phenolic compound content with a lower variation among samples (207.89 ± 2.18 mg GAE/100 g), compared to monofloral eucalyptus honeys (83.15 ± 4.09 mg GAE/100 g).…”
Section: Phenolic Compounds As Indicators Of the Botanical Origin Of Honeymentioning
confidence: 99%
“…In Kosovo, Ibrahimi & Hajdari, [ 104 ] observed a lower TPC in the multifloral acacia (25.76 ± 10.16 mg GAE/100 g) and chestnut (35.77 ± 8.26 mg GAE/100 g) honeys, but with a lower variation among samples, compared to the multifloral from meadows (46.48 ± 16.59 mg GAE/100 g) and forests (46.33 ± 18.95 mg GAE/100 g). Muñoz et al [ 56 ] reported that the wild multifloral of Peru registered a higher phenolic compound content with a lower variation among samples (207.89 ± 2.18 mg GAE/100 g), compared to monofloral eucalyptus honeys (83.15 ± 4.09 mg GAE/100 g).…”
Section: Phenolic Compounds As Indicators Of the Botanical Origin Of Honeymentioning
confidence: 99%
“…Los polifenoles totales se expresaron en mg de pinocembrina.Se determinó la absorbancia de la solución en un espectrofotómeto Jenway a 750 nm y se interpoló la absorbacnia en una curva de calibración elaborada con estándares comerciales de pinocembrina (6).…”
Section: Desarrollounclassified
“…A Agricultura 2,3,4,5,6,10,11,12,15,34,35,37,56,72,122,126,133,134,145,151,155,156,157,165,172,173,180,181,182,184,201,203,204,242 Android Studio 43,47,49 Animal nutrition 160,207,211,212,213,217…”
Section: íNdice Remissivomentioning
confidence: 99%
“…42 On the other hand, Muñoz et al observed that Peru’s multi-floral wild varieties of eucalyptus honey had the highest TPC with the most negligible variation (207.89 ± 2.18 mg GAE/100 g) in comparison with the monofloral types (83.15 ± 4.09 mg GAE/100 g). 43 However, among the monofloral varieties, MH found in Australia and New Zealand has the highest reported TPC with a value of 217–203 mg GAE/100 g. 44 In a study based on the variation of TPCs based on altitude, Nepalese honey showed the lowest TPC value of 61.77 mg GAE/100 g among honey harvested at >1,500 m from sea level compared to the honey harvested at 800–1,500 m from sea level, which showed a TPC of 118.65 mg GAE/100 g. 45 The TPC of honey also varies according to the climatic conditions. For example, in the case of Kenyan honey, the TPC of the honey was found to be 98.3777 mg GAE/100 g in the semiarid regions, 116.1777 mg GAE/100 g in the hot and humid area, and 141.7177 mg GAE/100 g in the high precipitation region.…”
Section: Introductionmentioning
confidence: 99%